Validity and Effectiveness of the Historical Electronics Module for Senior High School - Najuah, Najuah; Sidiq, Ricu; Azhari, Ichwan; Lukitoyo, Pristi Suhendro (History Department, Semarang State University and Historian Society of Indonesia, 2022)
This study examines the content validity and presentation of historical electronics modules (HEM) based on higher-order thinking skills developed with the ADDIE model for class XII high school students in Indonesia. In addition, the assessment of the effectiveness of the module on improving critical and analytical thinking skills through a competency test. The research method used is a mixed-method with research and development and experimental designs, starting from the development of the electronic history module and starting from Analysis, Design, Development, Implementation, and Evaluation. The results showed that the validity of the content and presentation from the experts and the users, in this case, students were very valid, so HEM was very suitable. The effectiveness test results showed increased students’ ability to think critically and analytically as an indicator of higher-order thinking. The electronic developed with a higher-order thinking approach can improve students’ ability to think critically and analytically in learning history independently. Penelitian ini mengkaji validitas isi dan penyajian modul elektronika sejarah (HEM) berbasis kemampuan berpikir tingkat tinggi yang dikembangkan dengan model ADDIE untuk siswa kelas XII SMA di Indonesia. Selain itu, penilaian keefektifan modul terhadap peningkatan kemampuan berpikir kritis dan analitis melalui uji kompetensi. Metode penelitian yang digunakan adalah metode campuran dengan desain penelitian dan pengembangan dan eksperimen, dimulai dari pengembangan modul sejarah elektronika) mulai dari Analisis, Perancangan, Pengembangan, Implementasi, dan Evaluasi. Hasil penelitian menunjukkan bahwa validitas isi dan penyajian dari ahli dan pengguna dalam hal ini siswa sangat valid, sehingga HEM sangat sesuai. Hasil uji efektivitas menunjukkan peningkatan kemampuan berpikir kritis dan analitis siswa sebagai indikator berpikir tingkat tinggi. Elektronik yang dikembangkan dengan pendekatan berpikir tingkat tinggi dapat meningkatkan kemampuan siswa untuk berpikir kritis dan analitis dalam pembelajaran sejarah secara mandiri. Cite this article: Najuah, Sidiq, R., Azhari, I., Lukitoyo, P.S. (2022). Validity and Effectiveness of the Historical Electronics Module for Senior High School. Paramita: Historical Studies Journal, 32(2), 286-294. http://dx.doi.org/10.15294/paramita.v32i2.30576